Sistem E-Filing dan Kepatuhan Wajib Pajak Orang Pribadi: Studi D&M IS Success Model pada KPP Pratama Denpasar Timur - Garnetia Pramanita, I Gusti Agung Ayu Ngr.; Ketut Rasmini, Ni (E-Jurnal Akuntansi, 2020)
This study aims to analyze the effect of information quality, system quality, service quality, use, and user satisfaction of e-filing systems on individual taxpayer compliance. This research was conducted by distributing questionnaires online and offline to e-filing individual taxpayers at KPP Pratama Timur Denpasar. The total sample is 100 individual taxpayers using convenience sampling techniques. The data analysis technique used is partial least square with SmartPLS 3.2.8 application. The results of this study indicate that information quality and system quality have a positive effect on the use of e-filing systems. Information quality, system quality and service quality influence the satisfaction of e-filing system users, the use and satisfaction of e-filing system users have a positive effect on taxpayer compliance. The results of this study can be used as input by the government in an effort to increase the use of e-filing by individual taxpayers. Keywords: E-filing; Updated D&M IS Success Model; Taxpayer Compliance.